Three members of the staff. Left: from Albania, right: from Italy, in the middle: Boris from Yugoslavia. Copied from collection Museum für Deutsche Geschichte
Three members of the staff. Left: from Albania, right: from Italy, in the middle: Boris from Yugoslavia. Copied from collection Museum für Deutsche Geschichte.